COMPANY FINANCIAL PERFORMANCE ANALYSIS BEFORE AND AFTER ACQUISITION ( CASE STUDY OF PT ELANG MAHKOTA TEKNOLOGI TBK) - ZAH, AZI; SE, MM, Harlendro (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aims to determine the differences in financial performance PT Elang Mahkota Teknologi Tbk before and after the acquisition. The variables used to measure the financial performance of liquidity ratios (CR and QR), the leverage ratios (DER, DAR, LTDFA), profitability ratios (ROA and ROE), growth ratios (Growth Increase Sales and Net Income), and the ratio of the value market (EPS and PER). Object of research is PT Elang Mahkota Teknologi Tbk year period 2009-2013. This research is a descriptive study describes the state of the financial performance of PT Elang Mahkota Teknologi Tbk before and after the acquisition using balance sheet, income statement and annual stock movement as a source of data. Data collection techniques used is the documentation, while for data analysis techniques using 11 financial ratios that have been mentioned. The results showed that the financial performance of the company after the acquisition activity has increased significantly, but also decreased compared to before the acquisition. It can be seen in the ratio of CR, QR, LTDFA, ROA, ROE, Sales Growth, EPS and PER showed an increase after the acquisition. While the ratio of DAR, DER and Growth of Net Income showed a decrease after the acquisition than before the acquisition. Keywords : financial performance, acquisitions, liquidity ratios, leverage, profitability, growth, market value.